Proses rekrutmen, seleksi, dan kompensasi terhadap kinerja tenaga pendidik di Madrasah Aliyah Swasta Se-Kota Bandar Lampung - Pertiwi, Mela Rosi; Hadiati, Etty (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2021)
The process of recruitment, selection, compensation and performance of educators is a factor in human resource management. As proper human resource management, one must be able to strive so that the workforce is placed in the right position according to their interests and abilities. The reality on the ground is that there are still educators who work not according to their educational background and are relevant in their fields, are recruited without knowing their duties and functions, do not have teaching readiness and are late in providing compensation by the madrasa. Various problems that exist will have an impact on the performance of educators, work results, quality services and timelines for achieving madrasa goals. The purpose of this study was to determine the effect of the recruitment, selection and compensation process on the power of optimizing the performance of educators in an educational institution. The research location is in Private Madrasah Aliyah (MAS) throughout Bandar Lampung City with a population of 13 MAS that are still active and have received operational permits for a long time with a sample of 70 respondents. Data collection techniques using a questionnaire in the form of google form and documentation. The data analysis technique uses a frequency test, classical assumption test with normality and multicollinearity tests, and multiple linear regression analysis. The results showed that there was an influence between the recruitment process on the performance of educators at MAS in Bandar Lampung by 55.6%. The results of the second study showed that there was no effect of selection on the performance of educators in MAS in Bandar Lampung, the significance value was 0.206. The results of the third study indicate that there is an effect of compensation on the performance of educators in MAS in Bandar Lampung by 57.3%. The results of the latest research show that there is an influence between the recruitment, selection and compensation processes on the performance of educators at MAS in Bandar Lampung by 64.0%.